Transborylation: borane-catalysed hydroboration and hidden catalysis - Bage, Andrew Dougal (The University of Edinburgh, 2022)
Hydroboration is a textbook reaction, finding application in total synthesis and the fine chemicals industry. The versatility of the organoborane products to be transformed into an array of different functionalities makes the reaction a valuable intermediary in multi-step syntheses. Traditionally, hydroboration was performed using stoichiometric borane reagents, but this was gradually superseded by transition metal-catalysed hydroboration systems. The established metal catalysts are typically based on scarce or expensive transition metals, of which some are toxic. When developing new catalysts for a known transformation, the system must provide a benefit over previous systems, be it through orthogonal reactivity, increased sustainability, or improved chemoselectivity, leading to increased potential to be used in late-stage functionalisation. A potential sustainable alternative to the standard transition metal catalysts is to use a catalyst based upon main-group elements. However, the traditional mechanisms of transition metal catalysis (oxidative addition and reductive elimination) cannot be easily applied to main group catalysts. Therefore, new turnover mechanisms are required to support the development of useful main-group catalysts. Transborylation is a redox-neutral turnover step that transforms stoichiometric borane reagents into catalysts, providing a platform to use the extensive knowledge base of stoichiometric borane reduction to develop new metal-free catalyst systems that could potentially rival transition metal catalysts. Transborylation has been used to develop a borane-catalysed hydroboration of alkynes with HBpin, showing impressive selectivity, and has been used to provide preliminary results for a borane-catalysed enantioselective hydroboration of alkenes. The importance of the hydroboration reaction has resulted in catalysed hydroboration becoming a benchmark with which to test new catalysts. Nucleophiles are abundant in catalyst architectures, as ligands and exogenous activators, and in catalysts that are inherently nucleophilic. Nucleophiles with structural similarities to known hydroboration catalysts were shown to mediate the decomposition of HBpin to active boron-based catalysts, which were the true catalysts of the hydroboration of alkynes and alkenes with HBpin. Hidden boron catalysis was shown to operate in systems for the hydroboration of alkynes and alkenes, previously proposed to be catalysed by nucleophilic catalysts.